French pharmaceutical industry and biologically active natural products from Pierre Fabre Laboratories - B, David,; R, Belle,; C, Dunouau,; P, Fleury,; P, Fleury,; -Pouny,, Granger; P, Negol,; M-J, Serrano, (Malaysian Journal of Science, 2000)
The industrial preparation and the bioactivity of the anticancer drug, Navelbine, were discussed. The active components of Ruscus aculeatus L., a plant used in the treatment of veinous insufficiency, were also mentioned. Structural elucidation of these compounds was reported.